Changes in Tear Lipid Layer Thickness and Symptoms Following the Use of Artificial Tears with and Without Omega-3 Fatty Acids: ARandomized, Double-Masked, Crossover Study - Fogt JS (Dove Medical Press, 2019)
Jennifer S Fogt,1 Nick Fogt,1 P Ewen King-Smith,1 Haixia Liu,2 Joseph T Barr1 1Ohio State University College of Optometry, Columbus, OH, USA; 2Allergan Plc, Irvine, CA, USACorrespondence: Jennifer S FogtThe Ohio State University College of Optometry, 338 West 10th Avenue, Columbus, OH 43210-1280, USATel +1 614-292-0882Email Fogt.78@osu.eduPurpose: To determine if an eye drop containing omega-3 fatty acids (Refresh Optive MEGA-3®, Allergan plc, Dublin, Ireland) increases the lipid layer thickness (LLT) of the tear film versus a non-emollient eye drop (Refresh Optive, Allergan plc).Methods: Patients (≥30 years) with baseline LLT ≤75 nm completed the Current Symptoms Survey (CSS – a visual analog survey of dry eye symptoms), and LLT was measured pre- and post-instillation (15 and 60 mins) of their randomly assigned treatment. After washout, patients were tested with the other treatment. Primary endpoint: change in LLT from baseline. Secondary endpoint: CSS results.Results: Of 21 patients enrolled, 19 completed the study. With the omega-3–containing eye drop, the mean (standard deviation) LLT increase from baseline at 15 mins was statistically significant in the overall field (8.8 [11.5] nm; P<0.001), and in each individual zone (superior, central, and inferior). At 1 hr, the LLT change from baseline was statistically significant overall (4.4 [9.7] nm; P<0.02) and in the inferior and central zones. With the aqueous eye drop, LLT change from baseline was only significant at 15 mins in the inferior field. The CSS analysis revealed a ≥8.68-unit decrease in mean average dryness score from baseline at 15 and 60 mins post-instillation of the lipid-based treatment (P≤0.03).Conclusion: The eye drop containing omega-3 fatty acids increased LLT at 15 mins, maintaining it at 1 hr post-instillation. Dryness symptoms also improved and maintained improved levels 1 hr after instillation, indicating that the product may benefit symptomatic patients with evaporative dry eye.Keywords: dry eye, artificial tears, ophthalmic solution, omega-3 fatty acids, survey, tear lipid layer